Examining personality and perceived trust on online purchase intention / Jamaliah Mohd. Yusof... [et al.] - Mohd. Yusof, Jamaliah; Ariffin, Shahira; Hassan, Nazatul Shyma (2014)
The current trend of online shopping among the consumers has shown an enormous growth. It is perpetually changing the way consumers and businesses interact with each other in the marketplace. In this regard, numerous studies could be found that investigated the online shopping of consumer behavior. Given the growing importance of online shopping among consumers, it remains imperative for the businesses to understand the factors that determine consumer behavior toward online shopping. Despite its widely studied, little academic attention is given to the personality traits - variety seeking, need to uniqueness, convenience preference, and innovativeness in the online shopping. Therefore, this study aims to offer insights by examining variety seeking, need to uniqueness, convenience preference, and innovativeness in influencing online purchase intention. In addition, this study extends its model by incorporating perceived trust variable in the personality and online purchase intention relationship. The findings revealed that perceived trust in an important variable that mediates only variety seeking and consumer preference types of consumers. The study also provided empirical support for a positive relationship between variety seeking, convenience preference and innovativeness of personality traits and perceived trust positive on online purchase intention. Need for uniqueness type of consumer was found to have no impact on online purchase intention. The results provide important findings to researchers and marketers by concluding that only certain types of consumer's personality have an influence on online purchase intention. The study also adds to the growing literature on the importance of perceived trust in the online shopping.